PENGGUNAAN ASAM LAKTAT SEBAGAI ACIDIFIER DALAM PAKAN YANG MENGANDUNG PROBIOTIK TERHADAP KONVERSI PAKAN DAN INCOME OVER FEED COST (IOFC) AYAM SENTUL BETINA - Ainina, Adika Nur; Hartoyo, Bambang; Rahayu, Sri (ANGON: Journal of Animal Science and Technology, 2021)
Backgrund. "Use of Lactic Acid as an Acidifier in Feed Containing Probiotics for Feed Conversion and Income Over Feed Cost (IOFC) of Sentul Females". The purpose of this study was to examine the effect of using an acidifier (lactic acid) in feed containing probiotics on feed conversion and income over feed cost (IOFC) of female Sentul chickens. Materials and Methods. The material used was 60 female Sentul chickens aged 6 months that were reared for 2 months. This research was conducted with an experimental method using a completely randomized design (CRD) consisting of 4 treatments and 5 replications, each replication consisting of 3 chickens. Treatment of adding acidifier in feed containing probiotics includes R0 (Basal ration without using an acidifier (BS), R1 (BS + Acidifier / lactic acid 0.5%), R2 (BS + Acidifier / lactic acid 1%), R3 (BS + Acidifier / lactic acid 1.5%). Results. The results of the analysis of variance showed that the use of an acidifier in feed containing probiotics had no significant effect (P> 0.05) on feed conversion and income over feed cost (IOFC) of female Sentul chickens. that the average feed conversion in treatment R0, R1, R2, R3 respectively is 3.03 ± 0.31; 3.00 ± 0.41; 3.07 ± 0.39; 2.84 ± 0.29, while for average income over feed cost (IOFC) in the treatment of R0, R1, R2, R3 respectively, namely 2,613.39 ± 1,537.32; 2,914.86 ± 2,161.92; 2,528.93 ± 1,504.26; 3,398.85 ± 1,498, 80. Conclusion. The conclusion of this study is that the use of acidifiers in feed containing probiotics has not been able to reduce feed conversion and increase IOFC of female Sentul chickens.